Evaluation of aleurone flour on dough, textural, and nutritional properties of instant fried noodles. (May 2020) - Xu, Min; Hou, Gary G.; Ma, Fengyun; Ding, Junzhou; Deng, Lingzhu; Kahraman, Ozan; Niu, Meng; Trivettea, Kathleen; Lee, Bon; Wu, Liang; Baik, Byung-Kee
Abstract: Aleurone flour is a nutrient-dense ingredient that can be incorporated into food products to improve nutritional and health benefits. The objective of this research was to evaluate dough and instant noodle quality using wheat flour/aleurone flour blends. Six blends of refined hard red spring wheat flour and aleurone flour at 100/0, 95/5, 90/10, 85/15, 80/20, and 75/25 blend ratios (g/g) were used to make instant noodles. Flour proteins increased by 3.7–13.1 g/kg with 50–250 g/kg aleurone flour substitution. Dough water absorption (65.6–75.4%) and mixing stability (15.2–17.6 min) were increased due to increased flour protein content after the inclusion of aleurone flour. However, the cooking yield of final instant noodle (142-127%) gradually declined with more aleurone flour substitution because of lower total starch and higher protein. Cooked noodle hardness (5.36–7.56 N) increased while springiness (0.962–0.937), cohesiveness (0.735–0.652) and resilience values (0.446–0.376) declined with increasing aleurone flour substitution due primarily to higher fiber content. Aleurone flour substitution for refined flour in instant noodle greatly increased total phenolic content and total dietary fiber content, effectively promoting its nutritional and health benefits to consumers. Highlights: Aleurone flour increased protein and mineral content of the flour blend. Aleurone flour substitution increased dough stability and reduced paste viscosity. Cooking yield, noodle color and texture were affected by aleurone substitution. Aleuorne flour significantly increased dietary fiber content of instant noodles. Aleurone flour significantly increased phenolics content of instant noodle.